POLITIK HUKUM REVISI UNDANG-UNDANG MAHKAMAH KONSTITUSI DIDASARKAN PADA JUDICIAL REFORM INDEX - Denethia Sausan (JURNAL EDUCATION AND DEVELOPMENT Institut Pendidikan Tapanuli Selatan, 2021)
An independent judiciary is one of the pillars of a rule of law. Independent in this case aims so that in carrying out its duties and authorities the judiciary stands alone without being influenced by other institutions. With the enactment of the revision of the Constitutional Court Law, it raises the question of whether the principle of independence that has been firmly held by the Constitutional Court is disturbed or the opposite. There is an urgency that needs to be regulated through the Constitutional Court Law but it is too much to be included in the substance. But issues that are not important are the main thing in this revision. To see the applicability of the principle of independence in the Constitutional Court, the Judicial Reform Index method is used to measure it.